Design of a hydraulically-driven bionic folding wing. (June 2018) - Zhang, Zhijun; Sun, Xuwei; Du, Pengyu; Sun, Jiyu; Wu, Yongfeng
Abstract: Membranous hind wings of the beetles can be folded under the elytra when they are at rest, and rotate and lift the elytra up only when they need to fly. This characteristic provides excellent flying capability and good environment adaptability. Inspired by the beetles, the new type of the bionic folding wing for the flapping wing Micro Air Vehicle (MAV) was designed. This flapping wing can be unfolded to get a sufficient lift in flight, and can be folded off flight to reduce the wing area and risk of the wing damage. The relationship between the internal pressures of the hydraulic system for the bionic wing folding varies and temperature was analyzed, the results show that the pressure within the system tends to increase with temperature, which proves the feasibility of the schematic design in theory. Stress analysis of the bionic wing was conducted, it was shown that stress distributions and deformation of the bionic wing under the positive and negative side loading are basically the same, which demonstrates that the strength of the bionic folding wing meets the requirements and further proves the feasibility of the schematic design. Graphical abstract: Inspired by the beetles, the new type of the bionic folding wing for the flapping wing Micro Air Vehicle (MAV) was designed. The folding/unfolding of the bionic folding wing are realized by the joint operation work of the hydraulic and elastic systems which various with different temperature.fx1 Highlights: The bionic folding wing are realized by combined the hydraulic and elastic systems. The pressure in the hydraulic system was growing with temperature. Simulation results confirm that the vein structure plays a vital supporting role.